Kontribusi Gaya Belajar Dan Motivasi Belajar Terhadap Hasil Belajar Bahasa Indonesia - Putri Ningrat, Sayu; Tegeh, I Made; Sumantri, Made (Jurnal Ilmiah Sekolah Dasar, 2018)
The aim of this study to know the contribution of learning styles and motivation of learning in result of learning Bahasa Indonesia in fifth grade student of SD Negeri Ularan Seririt Subdistrict in academic year 2017/2018. This study was ex-post facto research with total population as well as sample of 37 people. The data were collected through taking note document tecnique and questionnaire learning style and motivation of learning instrument. The data were analyzed in two steps, with descriptive statistic analysis and inferential statistic analysis through simple regression test and multiple regression test. The results showed that 1) learning style contribute 47.3% toward the result of learning Bahasa Indonesia as subject, 2) motivation of learning contribute 45.3% toward the result of learning Bahasa Indonesia as subject, 3) learning styles and motivation of learning contribute 62.8% in resulting of Bahasa Indonesia. In Contributing learning style and motivation of learning toward resulting of Bahasa Indonesia showed learning style and motivation of learning that was influential in resulting of the study Bahasa Indonesia at fifth grade students of SD Negeri Ularan Seririt Subdistrict in academic year 2017/2018